2018
DOI: 10.1186/s12864-018-4522-3
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analyses of the Chlamydia trachomatis core genome show an association between chromosomal genome, plasmid type and disease

Abstract: BackgroundChlamydia trachomatis (Ct) plasmid has been shown to encode genes essential for infection. We evaluated the population structure of Ct using whole-genome sequence data (WGS). In particular, the relationship between the Ct genome, plasmid and disease was investigated.ResultsWGS data from 157 Ct isolates deposited in the Chlamydiales pubMLST database (http://pubMLST.org/chlamydiales/) were annotated with 902 genes including the core and accessory genome. Plasmid associated genes were annotated and a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 63 publications
(94 reference statements)
4
28
0
Order By: Relevance
“…Indeed, we did not identify any SNPs that consistently differentiated ocular from urogenital trachoma isolates; the SNP found to be unique to ocular strains by Seth-Smith et al (2009) [16] was also found to occur in sporadic genotype G (G_S4658 and G_Ar246) and J (J_UK583676, J_UK35672, J_Soton72 and J_S42) isolates in the present dataset (these sequences were not available at the time of the earlier study). This reflects the close relatedness between these and trachoma (serovar A) plasmids previously noted [62], and may result from plasmid-swapping between strains, or recombination between plasmids; there is prior evidence of this from the present dataset [49]. Also, there is precedence for recombination between ocular and urogenital isolates [75] so the opportunity for genetic exchange must exist.…”
Section: Number Of 22 Bp Repeatsmentioning
confidence: 64%
See 3 more Smart Citations
“…Indeed, we did not identify any SNPs that consistently differentiated ocular from urogenital trachoma isolates; the SNP found to be unique to ocular strains by Seth-Smith et al (2009) [16] was also found to occur in sporadic genotype G (G_S4658 and G_Ar246) and J (J_UK583676, J_UK35672, J_Soton72 and J_S42) isolates in the present dataset (these sequences were not available at the time of the earlier study). This reflects the close relatedness between these and trachoma (serovar A) plasmids previously noted [62], and may result from plasmid-swapping between strains, or recombination between plasmids; there is prior evidence of this from the present dataset [49]. Also, there is precedence for recombination between ocular and urogenital isolates [75] so the opportunity for genetic exchange must exist.…”
Section: Number Of 22 Bp Repeatsmentioning
confidence: 64%
“…Advancements in genome sequencing technology over the past 20 years have shed light on many aspects of chlamydial biology and epidemiology, and with hundreds of whole genome sequences now in the public domain we have the ability to delve into the evolutionary history of C. trachomatis to a depth not previously possible. We now understand that modern lineages are the product of thousands of years of evolution rather than millions [49], and that the chlamydial plasmid has been vertically inherited throughout its evolutionary history, with very few instances of recombination or exchange between lineages [16,35,49,62]. Furthermore, through genetic manipulation and in vivo experiments, the role of each plasmid CDS in chlamydial virulence, regulation of gene expression and plasmid maintenance are gradually being revealed (Table 1).…”
Section: Number Of 22 Bp Repeatsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding molecular characterisation of sexually transmitted Ct strains, the knowledge gap is even more prominent. Globally, the emergence of new sexually transmitted strains and variants and their rapid spread indicate the need for more comprehensive molecular studies to better understand the Ct tissue tropism as well as epidemiological network structures [43][44][45]. Molecular assays targeting the ompA gene revealed that Ct genovars E and F are commonly found in Australian heterosexual men and women, while genovars G and D are the most common in MSM with genovar L2 also occurring [46].…”
Section: The Curious Molecular Epidemiology Of Ocular and Sexually Trmentioning
confidence: 99%